Assessment of the humoral immune status of varicella-zoster virus in patients with diffuse connective tissue diseases - Sun, Xiang; Zang, Yin-shan; Xu, Yan; Wang, Wen (Frontiers in Medicine, 2024)
Background: Diffuse connective tissue diseases (DCTDs) require long-term immunosuppressive treatment, increasing the risk of varicella-zoster virus (VZV) infection. This study aims to evaluate the humoral immune status against VZV in DCTD patients and explore factors that may influence their immune levels. Methods: This is a retrospective cohort study that collected data from adult DCTD patients (≥18 years) attending our outpatient clinic. The geometric mean concentration (GMC) of VZV-specific IgG antibodies in the patients' sera was measured using the enzyme-linked immunosorbent assay (ELISA). Results: A total of 280 RA patients, 272 SLE + MCTD patients and 280 healthy controls were included. SLE + MCTD patients had significantly higher VZV IgG antibody levels than RA patients (P < 0.05) but showed no significant difference compared to healthy controls (P > 0.05). Notable differences were observed particularly among female patients and those aged 30-49 years, (P < 0.05). SLE + MCTD patients in an active disease state had significantly higher VZV IgG antibody titers than RA patients (P < 0.05). Additionally, patients with a history of herpes zoster, regardless of being in the SLE + MCTD, RA, or control group, exhibited higher VZV IgG titers (P < 0.05). Conclusion: Although DCTD patients, particularly those with SLE and MCTD, exhibit higher VZV IgG antibody levels, they still face a higher risk of developing herpes zoster (HZ), which may be related to their underlying disease and immunosuppressive treatment. The presence of antibodies alone may not provide complete protection, necessitating consideration of cellular immune mechanisms. It is recommended to enhance monitoring of VZV antibody levels in high-risk patients and consider herpes zoster vaccination to reduce HZ-related complications.